2017
DOI: 10.1080/17483107.2017.1297858
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality exercise on a home-based phase III cardiac rehabilitation program, effect on executive function, quality of life and depression, anxiety and stress: a randomized controlled trial

Abstract: The virtual reality format had improved selective attention and conflict resolution ability, revealing the potential of CR, specifically with virtual reality exercise, on executive function. Implications for Rehabilitation In cardiac rehabilitation, especially in phase III, it is important to develop and to present alternative strategies, as virtual reality using the Kinect in a home context. Taking into account the relationship between the improvement of the executive function with physical exercise, it is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
186
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(194 citation statements)
references
References 42 publications
0
186
1
7
Order By: Relevance
“…Adherence was reported in two different ways: as dropout rates and/or as proportion of sessions/days completed. With respect to dropouts, only three studies 47,53,60 did not lose any participants, while six studies lost between 2.0% and 8.4%, 18,49,51,56‐57,59 three studies lost 12.7%‐17.9%, 55,58,61 one study lost 26.2%, 48 one study lost 28.3%, 50 and one study lost 43.8% 54 of the participants. When considering the proportion of intervention sessions/days attended by the participants, only seven studies reported data, 50‐51,54‐56,60,61 with attendance rates to the exergame intervention being ~30%, 56 62%, 54 63.9%, 60 ~77%, 50,55 and ~84% 51,61 .…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Adherence was reported in two different ways: as dropout rates and/or as proportion of sessions/days completed. With respect to dropouts, only three studies 47,53,60 did not lose any participants, while six studies lost between 2.0% and 8.4%, 18,49,51,56‐57,59 three studies lost 12.7%‐17.9%, 55,58,61 one study lost 26.2%, 48 one study lost 28.3%, 50 and one study lost 43.8% 54 of the participants. When considering the proportion of intervention sessions/days attended by the participants, only seven studies reported data, 50‐51,54‐56,60,61 with attendance rates to the exergame intervention being ~30%, 56 62%, 54 63.9%, 60 ~77%, 50,55 and ~84% 51,61 .…”
Section: Resultsmentioning
confidence: 96%
“…The number of participants in the studies varied from 15 60 to 88 52 . Two studies examined exclusively men, 47,50 three exclusively women, 32,51,60 while 11 studies assessed a mixed sex sample 18,48‐49,52‐56,58‐59,61 and one study did not report the participants’ sex 57 . In total, 236 men and 297 women participated in the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations